2014
DOI: 10.5539/ies.v8n1p71
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Metacognitive Reading Strategies Program for Improving Low Achieving EFL Readers

Abstract: As the training of language learners was a main concern of EFL teachers, this study aimed to assess the effectiveness of metacognitive reading strategies instruction (MRSI) on Taif University EFL students who achieved low results in reading. The final sample of this study was (21) female university students. The sample was divided into two groups; the experimental group, which consisted of (10) girls, and the control group, which consisted of (11) girls. By using the quasi experimental-research methodology, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 29 publications
6
24
0
Order By: Relevance
“…Ilustre (2011) also investigated if metacognitive reading strategies are better predictor of text comprehension and she found out that Problem Solving Strategies correlated positively with reading comprehension. Ismail and Tawalbeh (2015) conducted a quasi-experimental study examining the effect of the metacognitive reading strategies on EFL low achievers in reading. The study revealed that training on the use of metacognitive strategies among low achieving EFL readers improves reading comprehension performance.…”
Section: Metacognitive Reading Strategiesmentioning
confidence: 99%
“…Ilustre (2011) also investigated if metacognitive reading strategies are better predictor of text comprehension and she found out that Problem Solving Strategies correlated positively with reading comprehension. Ismail and Tawalbeh (2015) conducted a quasi-experimental study examining the effect of the metacognitive reading strategies on EFL low achievers in reading. The study revealed that training on the use of metacognitive strategies among low achieving EFL readers improves reading comprehension performance.…”
Section: Metacognitive Reading Strategiesmentioning
confidence: 99%
“…Students were able to grasp main ideas of reading texts better and they could make connections between reading passages and the world knowledge more effectively. Moustfa (2004, as cited in Ismail andTawalbeh, 2014) also carried out a study with 208 secondary school students on the effects of using metacognitive reading strategies on motivation and academic success. His findings showed that there was a positive relationship between academic achievement and metacognitive awareness of reading strategies.…”
Section: Awareness Of Reading Strategy Usementioning
confidence: 99%
“…As results, he argued that using reading strategies such as re-reading, underlining and circling of information helped students understand reading texts better. Ismail and Tawalbeh (2014) carried out a study with 41 EFL preparatory non-English major students on metacognitive reading strategies. were 122 ELT students.…”
Section: Awareness Of Reading Strategy Usementioning
confidence: 99%
See 1 more Smart Citation
“…Many research studies have probed the important role of listening strategy instruction and metacognitive listening strategies awareness in students' learning and achievement in various fields (Ismail & Tawalbeh, 2015;Mokhtari & Reichard, 2002;Yuksel & Yuksel, 2011). Sen (2009), for instance, examined the relationship between metacognitive strategy use and reading comprehension and found a marked improvement in learners' achievement.…”
Section: Listening Strategies Instructionmentioning
confidence: 99%